2019
DOI: 10.1051/0004-6361/201935760
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown curves of CH2(+), CH3(+), and CH4(+) molecules

Abstract: Aims. The aim of this work is to furnish branching ratios (BRs) to the kinetic databases used in astrochemistry such as the KInetic Database for Astrochemistry (KIDA). This concerns CHy(+) species (y = 2–4) excited by cosmic rays, electrons and photons, or the intermediate excited complexes CHy(+) resulting from a chemical reaction. Methods. The full set of fragmentation branching ratios following CHy(+) (y = 2,4) of constant velocity (250 keV uma−1) colliding with He atoms has been measured with the multidete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…and Attention is drawn to the nonlinear behavior of the relative intensity of the H band, which reflects the concentration of H atoms. As can be seen from the channels (1)-( 5) of CH 4 fragmentation, H atoms are formed in reactions ( 1), ( 3) and ( 4) with the branching ratios BR = 0.5; 0.2 and 0.1, respectively, for a photon energy of 9.8 eV and BR = 0.25; 0.5 and 0.2 for a photon energy of 12.1 eV according to [79], in which an analysis of energydependent branching ratios, the so-called breakdown curves, was presented. Let us analyze the reactions of secondary products of methane transformation CH 3 and CH 2 based on the data [79]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Attention is drawn to the nonlinear behavior of the relative intensity of the H band, which reflects the concentration of H atoms. As can be seen from the channels (1)-( 5) of CH 4 fragmentation, H atoms are formed in reactions ( 1), ( 3) and ( 4) with the branching ratios BR = 0.5; 0.2 and 0.1, respectively, for a photon energy of 9.8 eV and BR = 0.25; 0.5 and 0.2 for a photon energy of 12.1 eV according to [79], in which an analysis of energydependent branching ratios, the so-called breakdown curves, was presented. Let us analyze the reactions of secondary products of methane transformation CH 3 and CH 2 based on the data [79]:…”
Section: Resultsmentioning
confidence: 99%
“…Channel (10) does not operate (BR = 0) at this photon energy. It should be noted that H atoms that are formed in these reactions have an excess of kinetic energy, e.g., in channel (1), the experimental mean kinetic energy of the neutral lighter fragment H appeared to be 3.1 eV [79]. In most other channels, this energy exceeds 1 eV and such "fast" H atoms may diffuse for quite a long distance facilitating H + H recombination after thermalization.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] Due to these astrophysical motivations, most theoretical as well as experimental analyses have considered only the lowest energy fragmentation channel(s). [11][12][13] Under these conditions, cleavage of CÀ H bonds dominates that of CÀ C bonds [14,15] and it has been shown that the dominant paths depend little on the PAH size for sufficiently large molecules. [16] One common feature of PAHs is the larger abundance of the species with an even number of hydrogens compared to species with odd number of hydrogens.…”
Section: Contextmentioning
confidence: 99%
“…There is a considerable literature on CH + y hydrocarbon ions, and CH + 2 ions in particular, in the context of synthesis of hydrocarbons in the ISM (van Dishoeck et al 1996, van Dishoeck et al 2006, Wakelam et al 2010, Puglisi et al 2018, IdBarkach et al 2019. Significant work on CH + y hydrocarbon ions have also been done relevant to plasmas for fusion (Janev and Reiter 2002a, Janev and Reiter 2002b, Vane et al 2007, Lecointre et al 2009, Reiter and Janev 2010.…”
Section: Introductionmentioning
confidence: 99%